Escola Secundária Passos Manuel. Victor Mestre|Sofia Aleixo, vmsa arquitectos - Mestre, Victor (2012)
Situated in the historic centre of Lisbon, it was the first lyceum to be built in Portugal in the context of a broad educational reform promoted by Passos Manuel in 1836. Its 100 years history had been challenging changes in educational practice. Now a listed building, there was a need to renovate the school and introduce '21st century learning environments' while preserving the architectural heritage. In this Portuguese architectural annuary, edited by the architecture historian Michel Toussaint who choose 14 built works during 2010 in Portugal,a summary of the intervention along with images and schemes, provide an insight of the conservation intervention that took place under the authors design and supervision, between 2007 and 2010.